Local Self-Governments and the Vertical Division of Power - Varga, Ádám (Public Governance, Administration and Finances Law Review, 2022)
Local self-governments cannot be defined as entities against the state, nor do they merely assist in executing the central will. The significance of local self-governments lies in their role in the division and balancing of powers. In light of the principle of subsidiarity, the need for autonomy through decentralisation necessarily leads to the central bodies of the state being marginalised in these matters, in a sense, the latter lose their ability to solve the issues raised within their own sphere of competence. From a certain point of view, this can even be considered a vertical division of power. The division of executive power between the public administration subordinated to the Government and independent local self-governments, does not call into question the local self-government’s affiliation with the executive power. As such, it is practically an internal division of powers. In essence, it manifests itself as a kind of limited autonomy, which – due to the unity of the state – subsists only within the confines of the relevant laws. In light of the foregoing, jointly applied principles lead to a vertical division of power. Power is divided, which, nonetheless, does not mean that one sovereign body limits another; it is rather the case of the state restraining itself by virtue of the principle of democracy.